A review of material aspects in developing direct Z-scheme photocatalysts. (July 2021) - Li, Xuan; Garlisi, Corrado; Guan, Qiangshun; Anwer, Shoaib; Al-Ali, Khalid; Palmisano, Giovanni; Zheng, Lianxi
Graphical abstract: Abstract: Photocatalysis utilizes solar energy to produce clean fuels such as hydrogen or generate highly reactive species to subsequently break the organic pollutants into clean end products. Direct Z-scheme heterostructured photocatalysts can overcome the fundamental shortcomings in conventional photocatalysts and thus enable this green technology in tackling the energy crisis and environmental problems at the same time. Various approaches and numerous materials have been attempted in the hope of achieving high efficiency and broad effectiveness for practical applications. This work intends to provide a comprehensive and timely review on direct Z-scheme photocatalysts from the material's point of view. The formation mechanisms based on the driving forces of the charge transfer are firstly discussed to guide the material design. Three mechanisms, namely internal electric field, interfacial defect-induced charge transfer, and facet-induced charge transfer, are identified and summarized. Various material systems are then extensively discussed and compared according to their applications, followed by the emerging material modification strategies for performance improvement. Lastly, the review provides the perspectives for future development. It is expected that the insights of this up-to-date review could guide the material design and performance improvement of the direct Z-scheme systems to achieve their maximum potentials.